Determination of Groundwater Age in the Northeastern JIFARA Plain, LIBYA, Using Radiocarbon (C14) - Fatima Younes Altomi; Wafa Mohammed ALjdaei; Mohammed Altaher Milad (African Journal of Advanced Pure and Applied Sciences, 2026)
Jifara basin is a wide triangular area in the NE of Libya. This study represents some isotopic characteristics of groundwater in the NE Jifara basin, Libya. the results obtained from this study Were determination of age. geologic age, and the old climate in which the ground water had beer created by using the concentration of C14 in the samples. the Row data in this study was provided by General Water Authority Libya.